(untitled) (Journal of Information and Communication Technology, 2019)
User are confronted with information overload during searching for the information in virtual library. Studies claim that information overload leads to the changes in physiological signal of an individual which later result in decreased efficiency of information processing. There is a strong perception that when something changes, there is a moment at which the change occurs. The primary purpose of this research is to detect the existence of moment of the changes occur during searching in virtual library, which focusing on the pattern reflected in the physiological data that can potentially be used as indicator of a signal of information overload. This study adopts user testing methods and methods from psychophysiology. This paper presents result from quantitative analysis through graphs and tables. The results indicate that heart rate measurement is the best measure compare to other physiological measurement and the underlying pattern of the signal of information overload is presenting in a form of matrix. The recommendation of the future work is made which is the patterns can be used to design an application which monitor the information load among the individuals.